Analisa Perbandingan Pengaruh Pembebanan Elevator Terhadap Arus Listrik pada Motor Induksi Tiga Fasa dan Motor Permanen Magnet Tiga Fasa - Putra S, Rio; Abrianto, Heru; Gultom, Arlewes (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to analyze the electric current of elevators equipped with both three-phase induction motors and permanent magnet motors under varying load conditions (0%, 50%, and 90% of elevator capacity). Data was collected through direct observation using a Kyoritsu KEW 2007 current clamp. The results indicate that there is no significant difference in electric current and power consumption between 0% and 90% load conditions for both motor types. However, a notable difference was observed at the 50% load condition. The study suggests that permanent magnet motors are preferable due to their easier maintenance.